2014
DOI: 10.1038/jid.2014.19
|View full text |Cite
|
Sign up to set email alerts
|

Palmoplantar Keratoderma along with Neuromuscular and Metabolic Phenotypes in Slurp1 -Deficient Mice

Abstract: Mutations in SLURP1 cause mal de Meleda, a rare palmoplantar keratoderma (PPK). SLURP1 is a secreted protein that is expressed highly in keratinocytes but has also been identified elsewhere (e.g., spinal cord neurons). Here, we examined Slurp1-deficient mice (Slurp1−/−) created by replacing exon 2 with β-gal and neo cassettes. Slurp1−/− mice developed severe PPK characterized by increased keratinocyte proliferation, an accumulation of lipid droplets in the stratum corneum, and a water barrier defect. In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
52
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(58 citation statements)
references
References 66 publications
4
52
0
2
Order By: Relevance
“…Hyperkeratosis and triglyceride droplet accumulation can occur with genetic abnormalities in triglyceride hydrolysis, but they also occur in cases of run-of-the-mill dandruff. Recently, Adeyo et al (46) found lipid droplet accumulation with a deficiency of SLURP1, a secreted peptide of keratinocytes. Triglyceride hydrolysis in the epidermal keratinocytes is known to be important for producing the lipids for lamellar bodies, which play key roles in skin barrier function (47)(48)(49)(50).…”
Section: Discussionmentioning
confidence: 99%
“…Hyperkeratosis and triglyceride droplet accumulation can occur with genetic abnormalities in triglyceride hydrolysis, but they also occur in cases of run-of-the-mill dandruff. Recently, Adeyo et al (46) found lipid droplet accumulation with a deficiency of SLURP1, a secreted peptide of keratinocytes. Triglyceride hydrolysis in the epidermal keratinocytes is known to be important for producing the lipids for lamellar bodies, which play key roles in skin barrier function (47)(48)(49)(50).…”
Section: Discussionmentioning
confidence: 99%
“…Adeyo et al [70] show that SLURP-1 deficiency produces neuromuscular disorders in SLURP-1 knockout mice, in addition to the known cutaneous manifestations. This finding suggests that the SLURP-1 mutation in Mal de Meleda may be somehow localized to the epidermis or, alternatively, that there may be other phenotypic manifestations of Mal de Meleda not yet described.…”
Section: New Findingsmentioning
confidence: 99%
“…Secondly, there are findings that SLURP-1 is directly or indirectly involved in lipid hydrolysis, so when SLURP-1 is inactivated, this allows for increased neutral lipids in the stratum corneum. The combination of neutral lipid and fluid infiltrate creates an ideal medium for microorganism growth [70].…”
Section: New Findingsmentioning
confidence: 99%
“…Pharmacologic studies have supported that concept [24], but there is no clear evidence that SLURP1 binds to acetylcholine receptors, nor is it clear why perturbations in acetylcholine signaling would cause PPK. We showed that Slurp1 -deficient mice on a mixed C57/129 genetic background have PPK [5]. Interestingly, the knockout mice also exhibit hind-limb clasping [5], a phenotype that is often observed with neuropathy.…”
mentioning
confidence: 99%
“…We showed that Slurp1 -deficient mice on a mixed C57/129 genetic background have PPK [5]. Interestingly, the knockout mice also exhibit hind-limb clasping [5], a phenotype that is often observed with neuropathy. Because neurological disease is not thought to be a feature of mal de Meleda , the hind-limb clasping phenotype in mice was perplexing.…”
mentioning
confidence: 99%